What Homophobic Thinking Looks Like: Insights from New Zealand’s Homosexual Law Reform Debates of the Late 20th Century - Allan, Quentin (New Zealand Sociology, 2025)
“… wide range of homosexual manifestations … effeminate attitude, a mincing walk, the typical fairy … at the other extreme are the sodomites, and I do not believe that the majority of New Zealanders wish to be forced by law to accept a sodomite into houses that they own or even into their workplaces. …” Hon. Peter Tapsell (HRAB, 2R, NZPD, 27 July 1993) [voted against] This excerpt from a well-known and widely respected parliamentarian is indicative of deeply entrenched homonegative attitudes that were not unusual for the time—in fact, an accurate reflection of the mindset of many individuals throughout Aotearoa/New Zealand. In this article, I examine the Hansard transcripts of the New Zealand parliamentary debates around three parliamentary Bills: the Crimes Amendment Bill of 1974/75, the Homosexual Law Reform Bill of 1985/1986, and the Human Rights Amendment Bill (HRAB) of 1992/1993. From our contemporary vantage point, it is strange to reflect on a period when homonegative sentiments were so easily articulated, so diverse in content, and so seemingly correct in the mind of those who uttered them. The passage of time helps us to overlook much of what has happened in the past, but when we choose to focus on particular aspects of historical interest, forgotten details emerge with clarity. My objective in this article is to help us remember—or discover —the sorts of things that were said about ‘our people’ by members of parliament who opposed the legislation. In revisiting twentieth-century parliamentary discourse relating to homosexual law reform, we may find it surprising to apprehend the intensity and pervasiveness of societal homonegativity in Aotearoa/New Zealand last century. Applying the lens of Systemic Functional Linguistics, analysis of the text elucidates a homonegative discourse, with arguments based on ignorance and emotion, rather than logic or empirical evidence. This article contributes to our understanding of historical homonegativity in New Zealand, providing important implications for contemporary perspectives on LGBTQ+ issues.